2014
DOI: 10.1002/ejsp.2007
|View full text |Cite
|
Sign up to set email alerts
|

Society matters: The mediational role of social recognition in the relationship between victimization and life satisfaction among gay men

Abstract: This article examines the role of social recognition in the relationship between gay men's victimization and their life satisfaction. Using a comprehensive catalog of victimization, we obtained empirical evidence that strongly suggests that victimization negatively affects gay men's life satisfaction and that this relationship is mainly mediated by a perceived lack of social recognition in society. In addition, although active involvement in the gay community served as a coping mechanism, concealment of one's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 58 publications
3
17
1
1
Order By: Relevance
“…The ESIM argues that by acting in solidarity with other group members, individuals view their actions as effective and therefore feel empowered. Consistent with this, research in non‐gendered contexts (taxes, roads, HIV, homophobia) shows that collective action is positively predicts efficacy (Cocking & Drury, ), empowerment (Drury, Cocking, Beale, Hanson, & Rapley, ), life satisfaction (Bachmann & Simon, ), and physical/psychological well‐being (Molero, Fuster, Jetten, & Moriano, ). Experimental work also shows that signing a petition or email protest increases group efficacy (Van Zomeren, Drury, & Van Staaij, ) and positive affect (Becker, Tausch, & Wagner, ).…”
Section: Introductionmentioning
confidence: 66%
“…The ESIM argues that by acting in solidarity with other group members, individuals view their actions as effective and therefore feel empowered. Consistent with this, research in non‐gendered contexts (taxes, roads, HIV, homophobia) shows that collective action is positively predicts efficacy (Cocking & Drury, ), empowerment (Drury, Cocking, Beale, Hanson, & Rapley, ), life satisfaction (Bachmann & Simon, ), and physical/psychological well‐being (Molero, Fuster, Jetten, & Moriano, ). Experimental work also shows that signing a petition or email protest increases group efficacy (Van Zomeren, Drury, & Van Staaij, ) and positive affect (Becker, Tausch, & Wagner, ).…”
Section: Introductionmentioning
confidence: 66%
“…kood 12127191 Malle Tee 28, Mändjala 93871, Saaremaa, Kaarma Vald, Estonia distress leading to mental health problems. Many research studies have shown that individuals facing homophobia experience higher levels of anxiety and depression and are less satisfied with their lives (Bachmann & Simon, 2014;Feinstein, Goldfried, & Davila, 2012;Frost, Parsons, & Nanin, 2007;Meyer, 2003;Wight, LeBlanc, de Vries, & Detels, 2012). Besides its direct negative effects on homosexuals, homophobia has a wide range of less obvious negative social outcomes that affect heterosexuals as well, such as declining social capital (Andersson, 2011), hate crimes (Alden & Parker, 2005), teenage suicides (Poteat, Mereish, DiGiovanni, & Koenig, 2011), and school shootings (Kimmel & Mahler, 2003), to name only a few.…”
Section: Social Contextmentioning
confidence: 99%
“…Gays and lesbians are thus most suitable for the quantitative research we pursue here, although we by no means question the importance of (especially qualitative) research with less visible sexual minorities, such as bisexuals, transgender or intersex people. Moreover, our specific focus is on gays and lesbians in Germany where, despite much emancipatory progress in their favour over the last three decades, gays and lesbians are still the target of various forms of social, institutional and legal discrimination (Bachmann & Simon, 2014). For example, although civil partnership for same-sex couples was introduced in 2001, legal marriage and joint child adoption are still not possible for same-sex couples in Germany (Itaborahy & Zhu, 2014).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%